A3.06 Distinct expression pattern of peripheral tissue-restricted antigens in human LYMPH node stromal cells during the earliest phases of rheumatoid arthritis. (24th February 2016) - Hähnlein, J; Ramwadhdoebe, TH; Semmelink, JF; Safy, M; van Lienden, KP; Maas, M; Gerlag, DM; Tak, PP; Geijtenbeek, TBH; van Baarsen, LGM
Abstract : Background: In mice lymph node stromal cells (LNSCs) maintain peripheral tolerance through the presentation of peripheral tissue-restricted antigens (PTAs) and negative regulation of T-cells. However, little is known about PTA expression in human LNSCs. We hypothesise that deregulated expression of PTAs by human LNSCs might underlie the pathogenesis of autoimmune diseases like rheumatoid arthritis (RA). Objective: To investigate the expression and possibleregulation of several disease-related PTAsin human LNSCs derived from healthy donors and individuals having systemic autoimmunity. Methods: LNSCs were cultured from freshly collected lymph node needle biopsies obtained from 25 patients with rheumatoid arthritis (RA), 24 individuals positive for autoantibodies but without clinical apparent disease (RA-risk group) and 14 seronegative healthy controls. Expression of PTAs and the transcription factors DEAF1 and AIRE possibly regulating PTA expressionwere assessed by qPCR. Aire wasfurther investigated on protein level. LNSCs from five donors of each study group were stimulated with TNFα pluslymphotoxin α1β2 or poly (I:C) to study the regulation of PTA under inflammatory conditions. Results: Human LNSCs expressed the PTAs RRAD (Ras-related associated with diabetes), PLP1 (proteolipid protein 1), GAD1(glutamate decarboxylase 1) and the RA-related geneENO1 (Enolase 1(alpha)), but not AFP (alpha-fetoprotein). The expression of RRAD was slightly lower in RA-risk individuals which reached significance inRA patients (P = 0.04), especially in ACPA negativeRA patients (P = 0.0007). In contrast GAD1 mRNA levelswere significantly increased in RA-risk individuals (P = 0.01) with a trend towards increased expression in RA patients. Expression of ENO1 and PLP1 was similar in all donor groups. Invitro stimulation increased the expression of RRADin all donor groups to a similar extent. LNSCs express the transcription factors DEAF1andAIRE with Aire protein detected in the nucleus of LNSCs. Conclusion: Here we show for the first time that human LNSCs express disease-related PTAs as well as the transcription factors DEAF1and Aire, which supports their rolein tolerance induction. Already during the earliest phases of RA a differential PTA expression pattern is observed in LNSCs. Future studies are needed to investigate whether the distinct PTA expression pattern in LNSCs has an aberrant effect on T-cell regulation.